Pengendalian Kualitas Produk dengan Metode Statistical Quality Control untuk Mengurangi Produk Rusak pada UMKM Gethuk Anyar di Ngawi - Afifah Devi Lestari; Erni Widajanti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
MSMEs Gethuk Anyar is an industry operating in the culinary sector, the problem faced is the company's difficulty in maintaining the quality of the gethuk products it produces. This research aims to find out how quality control is implemented using statistical tools in an effort to control the quality and level of product damage at Gethuk Anyar MSMEs in Ngawi. Quality control analysis uses tools in the form of check sheets, cause and effect diagrams, Pareto diagrams and control charts. The results of the control chart analysis show that production is in an uncontrolled state. This can be seen from the control graph where the points fluctuate very highly and irregularly. Based on the Pareto diagram, priority repairs need to be made for the dominant types of damage, namely hard defects (59%), soft defects (27%), burnt defects (10%). From the analysis of the cause and effect diagram, it can be seen that the factors that cause damage originate from human/worker factors, work methods, production machines, work environment and raw materials so that companies can take preventive and corrective action in order to reduce the level of damage and improve product quality.